Intracranial Electrophysiology of Auditory Selective Attention Associated with Speech Classification Tasks - Nourski, Kirill V.; Steinschneider, Mitchell; Rhone, Ariane E.; Howard III, Matthew A. (Frontiers in Human Neuroscience, 2017)
Auditory selective attention paradigms are powerful tools for elucidating the various stages of speech processing. This study examined electrocorticographic (ECoG) activation during target detection tasks within and beyond auditory cortex. Subjects were nine neurosurgical patients undergoing chronic invasive monitoring for treatment of medically refractory epilepsy. Four subjects had left hemisphere electrode coverage, four had right coverage, and one had bilateral coverage. Stimuli were 300 ms complex tones or monosyllabic words, each spoken by a different male or female talker. Subjects were instructed to press a button whenever they heard a target corresponding to a specific stimulus category (e.g. tones, animals, numbers). High gamma (70-150 Hz) activity was simultaneously recorded from Heschl’s gyrus (HG), superior, middle temporal and supramarginal gyri (STG, MTG, SMG), as well as prefrontal cortex (PFC). Data analysis focused on (1) task effects (non-target words in tone detection vs semantic categorization task); and (2) target effects (words as target vs non-target during semantic classification). Responses within posteromedial HG (auditory core cortex) were minimally modulated by task and target. Non-core auditory cortex (anterolateral HG and lateral STG) exhibited sensitivity to task, with a smaller proportion of sites showing target effects. Auditory-related areas (MTG and SMG) and PFC showed both target and, to a lesser extent, task effects, that occurred later than those in the auditory cortex. Significant task and target effects were more prominent in the left hemisphere than in the right. Findings demonstrate a hierarchical organization of speech processing during auditory selective attention.